An update of prenylated phenolics: Food sources, chemistry and health benefits. (February 2021) - Chang, Sui Kiat; Jiang, Yueming; Yang, Bao
Abstract: Background: Prenylated phenolics, a type of important bioactive compounds, present with prenyl group on the phenolic skeleton. Prenylated flavonoids, stilbenoids, courmarins and xanthones are representive subclasses of prenylated phenolics with impressive bioactivities. These bioactive chemicals are presented in food sources and afford them great health benefits. Scope and approach: This review updates the prenylated phenolics identified from food sources. The sensory characteristics of dietary prenylated phenolics are highlighted. The bioavailabilities of dietary prenylated phenolics in relation to the health benefits in vivo are also discussed. Research findings on the health benefits of dietary prenylated phenolics from preclinical and clinical studies published within the last decade have been compiled and updated. Key findings and conclusions: Novel dietary prenylated phenolics (stilbenoids, flavonoids, coumarins and xanthones) isolated from food sources are presented. They show better bioactivities than the phenolic precursors. Dietary prenylated phenolics are bioavailable in human with impressive health benefits, including antioxidation, anti-diabetic activity, obesity prevention, cardioprotection, immunomodulation, neuroprotection and osteoprotection. It is worthy to mention that some prenylated phenolics have desirable taste and flavour. Inclusion of dietary prenylated phenolics into human diet is highly desirable since they are good nutraceuticals. Graphical abstract: Image 1 Highlights: Prenylated phenolics from food sources were compiled. Sensory characteristics of prenylated phenolics were discussed. Bioactivities of prenylated phenolics were presented.